IMPROVE THE RESPONSIBILITY OF STUDENT BY COOPERATIVE LEARNING MODEL TYPE JIGSAW AT SOCIAL STUDIES CLASS - Zakiah, Reza Rahma (Universitas Pendidikan Indonesia, 2019)
Â This research is initiated by the problem that happened at young learners at VII B Junior High School of Al-Inayah Bandung, it was founded by the researcher at her first observation, exactly the poor moral of responsibility students at social subject. This study conducted using the model of class treatment research designed by Kemmis and Mc. Taggart in three cycles. The selected alternative problem solving is using corporative research study jigsaw type. That alternative is recognized successful due to each of cycle significantly went through ascension, by gaining the cycle result I 64%, cycle II 76,2% and cycle III reached to 88,3%. In other side, the increasing of responsibility students can be showed by concerning the changes of each indicator, properly the learners can fulfill their compulsory well, stop fighting, avoid making any noises during learning process, achieve the satisfied learning result, behave as proactive during the learning process, persevering, independent and stop blaming other person and be able to accept othersâ€™ opinion during the discussion process. In a nutshell, the model of cooperative learning type jigsaw can improve the responsibility of students in learning social subject in VII B class Junior High School of Al-Inayah Bandung.Key words: The Model Of Cooperative Learning, Jigsaw and Responsibility.